Optimization and principles of acupoint selection and coordination in the treatment of adult abdominal obesity using acupuncture and moxibustion over the past decade: A data mining - Jia-xin SHEN; Tian-yun HUANG; Zhou HAO; Guang-bin PENG; Yue-ying MA; Huan-gan WU; Chun-hui BAO (World Journal of Acupuncture - Moxibustion)
Objective: To explore the optimization and principles of acupoint selection and coordination in the treatment of adult abdominal obesity using acupuncture and moxibustion over the past decade using data mining. Methods: Clinical studies of abdominal obesity treated with acupuncture and moxibustion, collected in the past 10 years, were searched from China Biology Medicine disc(CBMdisc), China National knowledge infrastructure (CNKI), Wanfang, China Science and Technology Journal Database(VIP), Pubmed, Embase, Google Scholar, Web of Science, (The Cumulative Index to Nursing and Allied Health Literature)CINAHL, Psyclnfo and Scopus, dated from March 1, 2013 to March 31, 2023. Using IBM SPSS Modeler 18.0 and other software, the frequency analysis, association-rules analysis and cluster analysis were conducted on interventions, traditional Chinese medicine(TCM) patterns, use frequency of acupoint, meridian attribution of acupoint, acupoint location, etc. Results: A total of 55 articles were included, with 102 prescriptions and 71 acupoints involved. The top 3 interventions were acupoint embedding method, simple electroacupuncture and simple filiform needling. Seventeen patterns/syndromes of TCM differentiation were collected, dominated by spleen deficiency and damp blockage, spleen and kidney yang deficiency and heat accumulation in stomach and intestines. The acupoints in clinical practice were mostly at the foot-yangming stomach meridian, the conception vessel and the foot-taiyin spleen meridian, and located at the abdominal region. The top 5 acupoints of high frequency were Tianshu (ST25), Zhongwan (CV12), Daheng (SP15), Zusanli (ST36), Huaroumen (ST24) and Daimai (GB26). The specific points of the high frequency were the crossing points and front-mu points, of which, ST25 and CV12 were the most prominent. After association-rules analysis on the high-frequency acupoints, 20 groups of associated acupoints were obtained, in which, the core acupoints included ST25, CV12, SP15 and ST36. Conclusion: In recent 10 years, abdominal obesity is treated by the acupoints of foot-yangming stomach meridian, the conception vessel and the foot-taiyin spleen meridian. Compared with the regimen for simple obesity, the acupoints at the abdominal region are specially selected in treatment of abdominal obesity, such as ST25, CV12, SP15 and ST36. Supplementary acupoints are selected based on syndrome differentiation to simultaneously address both the disease manifestations and root causes.